The UK clinical eye research strategy: refreshing research priorities for clinical eye research in the UK - Bourne, Rupert R. A.; Moledina, Malik; Azuara-Blanco, Augusto; Saleh, George M.; Self, James E.; Sivaprasad, Sobha; Sharma, Srilakshmi M.; Ross, Andrew; Gilbert, Rose M.; Abdalla Elsayed, Maram E. A.; Moon, Won Young; Doug, Manjo; et al. (Eye (London), 2024)
Objectives To validate and update the 2013 James Lind Alliance (JLA) Sight Loss and Vision Priority Setting Partnership (PSP)’s research priorities for Ophthalmology, as part of the UK Clinical Eye Research Strategy. Methods Twelve ophthalmology research themes were identified from the JLA report. They were allocated to five Clinical Study Groups of diverse stakeholders who reviewed the top 10 research priorities for each theme. Using an online survey (April 2021-February 2023), respondents were invited to complete one or more of nine subspecialty surveys. Respondents indicated which of the research questions they considered important and subsequently ranked them. Results In total, 2240 people responded to the survey (mean age, 59.3 years), from across the UK. 68.1% were female. 68.2% were patients, 22.3% healthcare professionals or vision researchers, 7.1% carers, and 2.1% were charity support workers. Highest ranked questions by subspecialty: Cataract (prevention), Cornea (improving microbial keratitis treatment), Optometric (impact of integration of ophthalmic primary and secondary care via community optometric care pathways), Refractive (factors influencing development and/or progression of refractive error), Childhood onset (improving early detection of visual disorders), Glaucoma (effective and improved treatments), Neuro-ophthalmology (improvements in prevention, diagnosis and treatment of neurodegeneration affecting vision), Retina (improving prevention, diagnosis and treatment of dry age-related macular degeneration), Uveitis (effective treatments for ocular and orbital inflammatory diseases). Conclusions A decade after the initial PSP, the results refocus the most important research questions for each subspecialty, and prime targeted research proposals within Ophthalmology, a chronically underfunded specialty given the substantial burden of disability caused by eye disease.